Quantifying components of the energy balance of a maize and bean intercrop - Gebrekristos, Solomon Afeworki (University of the Free State, 2003)
Quantification of the energy balance components is useful to enable analysis of irrigation scheduling and water use efficiencies in addition to calibration and validation of crop models. An experiment was conducted at Bainsvlei, Bloemfontein during the rainy season (January to April) of 2003 to quantify the energy balance components and determine the phenology of maize and bean crops within the intercropping system. The Bowen ratio energy balance method was used to quantify the components of the energy balance. Net radiant flux (Rn, soil heat flux (G), wet and dry bulb temperature and other meteorological variables were measured. The energy balance components were estimated from day of year (DOY) 47 to 79 and classified based on the height of instrument in four datasets as follows:- from DOY 47 to 58, 59 to 69, 70 to 79 and 90 to 100. During the last period (90 to 100 DOY) measurements were made over bare soil, as the crop was harvested following a hailstorm. Data collected on Cloudy days and where β approached -1 were excluded from the analysis. It was found that the latent heat flux was low throughout the crop growing season. This was mainly due to soil water stress, rather than energy availability. More than 57% of the energy was utilized in generating sensible heat flux rather than for evapotranspiration. Average net radiation inputs were 1.60±0.31 MJ m-2, 1.69±0.15 MJ m-2 , 1.19±0.57 MJ m-2 and 1.20±0.20 MJ m-2respectively, for the datasets as classified above. The average latent heat fluxes as a fraction of the net radiation during these times were 0.30Rn, 0.37Rn, 0.41Rn and 0.65Rn. The average sensible heat fluxes as a fraction of the net radiation were 0.56Rn, 0.50Rn, O.48Rn and O.22Rn for datasets as mentioned above respectively. The soil heat flux was on average 13.2% of net radiation throughout the time of measurement. Comparison of ET calculated from Bowen ratio and FAO Penman-Monteith equation showed significant difference for the hourly values. However, there was no significant difference at the daily time scale. This suggests that the methods might be complimentary for estimating ET for a long period of time, using the range of a day or more. The phenology of maize and bean was monitored during the vegetative period. It was found that the maize accumulated 90 °Cd from planting to emergency, 408 °Cd from emergency to tassel initiation and 258 °Cd from tassel initiation to vegetative stage and 243 °Cd from Rl (50% of plants have at least one flower at any node) to R4 (50% of plants have pods with seeds at beginning of pod filling stage). The maize exhibits a delay in its development even if the required growing degree-days were accumulated due to the severe water stress. However the development of the bean was not affected by the competition involved in the intercropping system both for water and light.

Kwantifikasie van die energiebalanskomponente is bruikbaar om analise van besproeiingskedulering en watergebruiksdoeltreffendheid, sowel as kalibrasie en validasie van gewasmodelle uit te voer. 'n Eksperiment is te Bainsvlei, Bloemfontein gedurende die reënseisoen (Januarie tot April 2003) uitgevoer om die energiebalanskomponente te kwantifiseer en om die fenologie van mielie en boongewasse binne die tussengewassisteem te bepaal. Die Bowen verhouding energiebalansmetode is gebruik om die komponente van die energiebalans te kwantifiseer. Nettostralingsvloed (Rn), grondhittevloed (G), droë en natbol temperatuur en ander meteorologiese veranderlikes is gemeet. Die energiebalans komponente is bereken vanaf dag van jaar (DOY) 47 tot 79 en geklassifiseer volgens hoogte van instrument in vier datastelle: van DOY 47 tot 58, 59 tot 69, 70 tot 79 en 90 tot 100. Gedurende die laaste periode (90 tot 100 DOY) is lesings op kaal grond geneem omrede die gewas na 'n haelstorm geoes is. Data versamelop bewolkte dae, waar β -1 nader, is nie by die analise ingesluit nie. Daar is gevind dat die latente hittevloed regdeur die gewas groeiseisoen laag is. Die het plaasgevind hoofsaaklik as gevolg van grondwaterstres , eerder as energie beskikbaarheid. Meer as 57 % van die energie is gebruik om aanvoelbare hittevloed, eerder as vir evapotranspirasie te genereer. Gemiddelde nettostra-lingsinsette is 1. 60±0. 31 MJ m-2, 1. 69±0. 15 MJ m-2 , 1.19±0.57 MJ 1. 20±0. 20 MJ m-2 respek-tiewelik vir die datastelle soos hierbo geklassifiseer. Die gemiddelde latente hittevloed as 'n fraksie van nettostraling gedurende hierdie tye was 0.30Rn, 0.37Rn, 0.41Rn en 0.65Rn. Die gemiddelde aanvoelbare hittevloed as 'n fraksie van die nettostraling is O. 56Rn, 0.50Rn, O.48Rn en O.22Rn vir datastelle voorheen genoem. Die grond-hittevloed regdeur die totale tydperk van lesingopis gemiddeld 13.2 % van die nettostraling. Vergelyking van ET bereken vanaf Bowen verhouding en FAO Penman-Monteith vergelyking, het noemenswaardige verskille vir uurlikse waardes gedemonstreer. Daar is nietemin geen noemensw-aardige verskilop die daaglikse tydskaal gewaar nie. Die voorstel wat hieruitspruitis dat die metodes komplimentêr van aard vir ET oor 'n lang tyderk mag wees, indien 'n reeks van 'n dag of meer gebruik word. Die fenologie van beide mielies en bone is gedurende die vegetatiewe fase gemonitor. Daar is gevind dat mielies 90 °Cd vanaf plant tot opkoms, 408 °Cd vanaf opkoms tot pluimverskyning, 258 °Cd vanaf pluimsverskyning tot baardverskyning geakkumuleer is. Bone het 513 °Cd geakkumuleer om die vegetatiewe fase te voltooi en 243 °Cd vanaf Rl (50 % plante het ten minste een blom by enige knoop) tot R4 (50 % plante het peule met sade by die begin van die peulvullingstadium) . Die mielies vertoon 'n agterstand in ontwikkeling as gevolg van ernstige water-stres, al is die vereiste groeigradedae geakkumuleer. Nietemin is die ontwikkeling van bone in die tussengewas-sisteem nie deur kompetisie vir beide water en lig beinvloed nie.
Dissertation (M.Sc.Agric. (Soil, Crop and Climate Sciences))--University of the Free State, 2003
Keywords: Corn -- South Africa -- Bloemfontein; Beans -- South Africa -- Bloemfontein; Intercropping -- South Africa -- Bloemfontein